The Correlation Among the Immunoglobulin G Synthesis Rate, IgG Index and Albumin Quotient in Guillain-Barré Syndrome and Chronic Inflammatory Demyelinating Polyradiculoneuropathy: A Retrospective Case–Control Study - Tu, Yu; Gong, Xuan; Zhang, Yuanyuan; Peng, Jiewei; Zhuo, Wenyan; Yu, Xueying (Frontiers in Neurology, 2021)
Background The immunoglobulin G synthesis rate (IgG SR) and immunoglobulin G (IgG) index are indicators of abnormal intrathecal humoural immune responses, and the albumin quotient (QALB) is an indicator used to evaluate the completeness of the blood-cerebrospinal fluid barrier (BCB). There are no systematic reports concerning differences in Guillain-Barré syndrome (GBS) and chronic inflammatory demyelinating polyradiculoneuropathy (CIDP). We assessed the differences in the IgG SR, IgG index and QALB between GBS and CIDP patients in a Chinese cohort. Methods We retrospectively collected data from 167 patients with GBS and CIDP. The IgG SR, IgG index and QALB were calculated using formulas. The relevant clinical data were subjected to a statistical analysis. Results Of the GBS and CIDP study groups, the QALB had the highest positive rate (80.00%) in the CIDP group (P<0.01). The QALB stratification analysis showed that the ranges of 10~30 were dominant in the GBS and CIDP groups, and the positive rate of CIDP was higher than that of GBS. furthermore, QALB≤7 was dominant in the GBS group, and QALB>30 was dominant in the CIDP group. In the receiver operating characteristic (ROC) curve analysis with the CIDP group as the trial group and the GBS group as the control group, the differences in QALB were statistically significant (P<0.01). To achieve a high specificity of 98~99%, the diagnostic cut-off value for QALB was above 57.37 (sensitivity: 9.33%) or below 0.60 (sensitivity: 4.35%). The multivariate logistic regression analysis showed that the number of CIDP patients with QALB was higher than 57.37, and compared with the GBS patients, the difference in QALB was statistically significant (P<0.01). Conclusion The elevation in QALB was associated with CIDP, while QALB values above 57.37 or below 0.60 had high specificity in differentiating between GBS and CIDP. In CIDP, the BCB is generally moderately to severely damaged; in GBS, the BCB is generally mainly moderately damaged.